BRIDE VALUE: A FEMINIST READING OF BUCHI EMECHETA’S THE BRIDE PRICE - Zanyar Kareem Abdul (Universitas Islam Sumatera Utara (UISU), 2019)
The Bride Price is one of the most influential modern novels authored by Buchi Emecheta through which the voice of a female character is expressed. The study has two points of discussion: the first deals with patriarchal society in which women suffer and become the only victims, and the second does with African culture from which Emecheta criticizes severely. Men have all the powers in controlling the whole family. The traditional society of Africa follows their culture as it is especially in paying the bride from the groom’s family. The paper aims at both men and women to keep this belief for the rest of their life no matter how modern the society has become. To some extent, the idea of “double colonization” proposed by Peterson and Rutherford (1986) will be identified in the paper and further explanation will be given. The paper also is an attempt to analyze the reflection of the African system related to marriage in the novel; as similar idea can be found in Iraqi Kurdistan that would be counted as the main objective behind writing the current paper. Furthermore, it shows some cultural similarities between both countries. By applying “double colonization” theory, the researcher confirms that Emecheta’s female characters suffer a traumatic experience in which they are controlled by two colonizers: the power of males and the reality of colonization. The researcher tries to send his messages through this paper out to avoid such conflicts and spread self and cultural awareness among the society.